2018
DOI: 10.1007/s00198-018-4654-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene-based GWAS analysis for consecutive studies of GEFOS

Abstract: Purpose Single-nucleotide polymorphism (SNP)-based genome-wide association studies (GWASs) have already identified about 100 loci associated with bone mineral density (BMD), but these loci only explain a small proportion of heritability to osteoporosis risk. In the present study, we performed a gene-based analysis of the largest GWASs in the bone field to identify additional BMD-associated genes. Methods BMD-associated genes were identified by combining the summary statistic P values of SNPs across individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…Another useful approach is that used in gene-based GWAS, which regard a gene as a basic unit for association analyses, thereby improving the statistical power (BOX 2) by overcoming the potential allelic heterogeneity (BOX 1) and reducing the number of independent statistical tests from millions (for SNPs) to tens of thousands (for genes) 44 . A 2018 study found three novel BMD-associated genes (UBTF, AAAS and C11orf58) through a gene-based GWAS strategy 44 . The roles of the proteins encoded by these three genes in bone homeostasis are still unknown.…”
Section: Susceptibility Loci Derived From Gwasmentioning
confidence: 99%
“…Another useful approach is that used in gene-based GWAS, which regard a gene as a basic unit for association analyses, thereby improving the statistical power (BOX 2) by overcoming the potential allelic heterogeneity (BOX 1) and reducing the number of independent statistical tests from millions (for SNPs) to tens of thousands (for genes) 44 . A 2018 study found three novel BMD-associated genes (UBTF, AAAS and C11orf58) through a gene-based GWAS strategy 44 . The roles of the proteins encoded by these three genes in bone homeostasis are still unknown.…”
Section: Susceptibility Loci Derived From Gwasmentioning
confidence: 99%
“…A transcriptome-based SNP approach can be a cost/time-saving method for identifying large-scale markers 37 . We found 9 transcriptome-wide SNPs in the coding regions associated with flower color (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptome-based SNP approach can efficiently address these problems. Additionally, transcriptome-based GWAS represents a cost-effective and time-saving method for developing large-scale markers 16 , especially compared with the general GWAS or other conventional marker identification assays. Recently, transcriptome-based GWAS has been successfully applied to human diseases 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, genome-based breeding reduces the time required for various breeding schemes 14,15 . Furthermore, a transcriptome-based GWAS, which is a type of GWAS, uses transcriptome sequencing data to identify variants within the coding regions of the genome 16 . Transcriptome-based GWAS has several advantages compared with the traditional GWAS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation